Continuous Intra-Incisional Bupivacaine for Postoperative Analgesia after Hip Nailing Surgery: A Randomized Clinical Trial - Arash Farbood; Sanaz Abbasi; Naeimehossadat Asmarian; Mahsa Banifatemi; Vida Naderi-boldaji; Zeinabsadat Fattahi Saravi (Pain Research and Management)
Background. The effectiveness of continuous wound infiltration (CWI) as a postoperative pain-control technique has been shown in many surgical procedures. This study investigates the effect of CWI of local anesthetic on postoperative pain control in intertrochanteric fracture patients undergoing hip nailing surgery. Methods. In this randomized clinical trial, 48 patients who were scheduled for hip nailing surgery were randomly assigned to receive (n = 24) or not receive (n = 24) bupivacaine infusion through a catheter inside the surgical wound, postoperatively. Pain intensity (NRS), required dose of morphine, and drug-related complications within 24 hours of the intervention were assessed and compared. Results. Pain intensity was significantly lower in the bupivacaine group both during the recovery room stay and in the ward in the first 24 hours after the procedure (P<0.001). In the recovery room, the control group patients had a higher morphine consumption compared to the bupivacaine group (P<0.001) and requested it earlier than the bupivacaine group (60 (45–60) vs. 360 (195–480) minutes) (P<0.001). In the ward, all control group patients used the PCA morphine pump, while only 54% of the bupivacaine group self-administered morphine through the pump, with a significantly lower total morphine consumption (1 (0–2) vs. 10 (5–14) mg, P<0.001). None of the patients in the bupivacaine group required additional morphine, while 37.5% of the control requested additional morphine (P=0.002). Altogether, the control group had a higher total morphine consumption compared to the bupivacaine group in the first 24 hours (10.5 (6–15.5) vs. 1 (0–2) mg, P<0.001). Conclusion. CWI of bupivacaine helps better pain reduction during the early postoperative hours while it reduces opioid consumption, minimizes nausea and vomiting, and improves patient satisfaction.